PENERAPAN MODEL PEMBELAJARAN INKUIRI BERBANTUAN LUPIKA TERHADAP PEMECAHAN MASALAH SISWA SD KELAS 4 SD - Lahagu, Anania; Yunitiara Rizqi, Hesti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low problem-solving ability of elementary school students remains a major issue in mathematics learning, mainly due to teacher-centered instruction and limited use of innovative learning media. This study aims to examine the effect of the inquiry learning model assisted by Lupika media on fourth-grade students’ problem-solving ability. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The participants were fourth-grade students of SD Negeri Karangjati 04, divided into an experimental class and a control class. Data were collected through problem-solving ability tests, student response questionnaires, and observation sheets of learning implementation. The data were analyzed using an independent sample t-test and simple linear regression analysis. The results indicate a significant difference in problem-solving ability between students taught using the inquiry learning model assisted by Lupika media and those taught using conventional learning. Furthermore, the inquiry learning model assisted by Lupika media has a positive and significant effect on students’ problem-solving ability. These findings suggest that integrating inquiry-based learning with educational game media enhances student engagement, conceptual understanding, and logical thinking skills in solving mathematical problems. Therefore, the inquiry learning model assisted by Lupika media is effective and can be used as an alternative learning strategy to improve elementary students’ mathematical problem-solving ability.